Home language use and shift in Australia: Trends in the new millennium - Zhang, Lubei; Tsung, Linda; Qi, Xian (Frontiers in Psychology, 2023)
The 25 million Australians today are identified with more than 290 ancestries. People’s home language use and shift patterns had demonstrated great variations as more immigrants from Asia-Pacific regions entered Australia. The ethnolinguistic composition of Australia’s population had undergone substantial changes in the last few decades. Based on the statistics from Australian censuses, the present paper aims to analyze the changes of people’s home language use and the shift patterns in the new Millennium. Five sets of census data released by Australian Bureau of Statistics were adopted as the secondary data source and descriptive analysis was conducted to disclose the dynamic picture of different home languages in Australia after 2000. The results suggest that the number of home language speakers in Australia has soared up quickly in the last two decades and great variations have been found between the traditional European migrant groups and the newly Asian arrivers. Mandarin has overtaken Italian and Greek to become the most populous home language other than English used in Australia since 2011 and great regional differences were also found to exist among different states and territories. Moreover, the ranking order of different home language speakers had changed considerably as compared with that in the last century. The language shift rates of different language communities and their cross-tabulations with generations, gender, age and duration of residence in the latest available censuses after 2000 also revealed diverse developmental directions. The findings give us a glimpse of the current status of different home languages in Australia and help us to identify the potential factors impacting the shifting trends of different language communities. A better understanding of the language needs of different migrant communities may further help policy makers set more effective plans to accommodate an increasingly diverse Australian society.